A total cost of ownership comparison of log truck decarbonization in pulp mills supply chain - Moura, Ângelo Conrado de Arruda (2024)
Global carbon dioxide (CO2) emissions from energy combustion and industrial processes have increased by more than 80% in the last 30 years. Many efforts are being made to set policies and international targets to reduce Greenhouse Gas Emissions (GHG). Globally, transport accounts for 30% of final energy consumption and still has only 4.1% based on renewable sources (REN21, 2023). Thus, decarbonization is a critical challenge, especially in long-distance heavy duties vehicles, as non-fossil fuel technologies are not mature enough for large-scale implementation. A broad list of alternative fuel technologies is being developed and gradually introduced, from ethanol, bioDiesel, Hydrotreated Vegetable Oil (HVO), biomethane, natural gas (compressed or liquified), electric hydrogen fuel cells, hybrids, and fully electric vehicles. The pulp and paper sector has the wood fibers from the planted forest as the primary and renewable power source, energy self-sufficiency, and generating surplus, usually sold to the market. On the other hand, Diesel consumption in log transportation is the highest in the pulp production chain. Therefore, this study analyzed the potential application of promising low-emission heavy-duty trucks for log transportation in a Brazilian pulp industry integrated into the pulp mill energy generation. Due to the uncertainty of several variables, a sensitivity analysis was performed to check costs and benefits using the Monte Carlo simulation. The results show the Electric truck option with lower Total Cost of Ownership (TCO) per kilometer, 1.52 USD/Km; gas options LNG, 1.59 USD/Km and CNG, 1.73 USD/Km; Diesel with 1.87 USD/Km and highest cost for Fuel Cell, with 2.02 USD/Km. The main inputs impacting the results were fuel costs and distance. Despite lower TCO, the Electric truck option has a negative Return on Investment (ROI), meaning the investment is higher than the benefits. The Liquified Natural Gas (LNG) solution was the only one that had a positive ROI. Although Electric Heavy Duty Truck (BEV) still does not have a positive ROI, it is the simplest solution to connect with energy from pulp mills and is expected to have the highest market share. Therefore, it can potentially be the first position in renewable truck options in pulp mill operations in the medium to long term.